Experiencing police violence and insults: narratives from ethnic minority men in Denmark. Issue 2 (2nd July 2020) - Birk Haller, Mie; Kolind, Torsten; Hunt, Geoffrey; Søgaard, Thomas Friis
ABSTRACT: Young men living in socially deprived areas are more likely to be exposed to criminal activity and extraordinary policing measures. This article focuses on the narratives of police encounters told by ethnic minority young men living in a deprived neighbourhood in Denmark, defined by the Danish government as a 'ghetto'. In total, 76 young men and 6 young women (age 15 to 26) were interviewed between 2016 and 2017. The article focusses on their experiences of the police's use of force, interpreted as violence by the participants. We have categorized their experiences into three types: unnecessary use of force, inconsistent violence, and humiliation/insults. While police violence is often understood as primarily physical, we also show that in the young people's recollections of these incidences, issues of 'moral violence' becomes important. While not only specifically violating the body, this type of violence also affects the integrity and dignity of individuals. Our participants recounted forms of violence, which were extra-judicial in terms of physical use of force and they described how the police used indirect and degrading techniques of violence, some of which can be categorized as sexual harassment, embarrassment and public humiliation. From their perspectives, police power appeared unpredictable and illegible.